Gestión de la seguridad y comportamiento de los trabajadores en instalación de sistemas contra incendios en el Mall Aventura Iquitos Loreto – 2023 - Inuma Gonzales, Elmer (2024)
The objective of the research was to analyze safety management with the behavior of workers in the installation of fire protection systems at Mall Aventura Iquitos. It is a quantitative research of the non-experimental, descriptive, exploratory, analytical and transversal type. The information collection instrument was a structured survey using the Likert scale, where the workers of the company IDT Ingeniería SAC indicated their level of agreement or disagreement about Safety Management and Worker Behavior. The reliability of the “Cronbach's Alpha” instrument was 0.731. To improve the analysis and interpretation, the procedure of grading or construction of assessment scales was used, converting the Likert scale responses into percentages that represent three levels of evaluation: "low", "medium" and "high", based on This was carried out in inferential analysis in SPSS 26, to measure the normality of the data using the Shapiro Wilk normality test and to determine the relationship between variables, the Pearson statistic was used and which allowed the following conclusions: Security management in installation procedures for fire protection systems in Mall Aventura Iquitos, was rated as high, because they consider that the installation procedures for fire protection systems have clear information about safety measures, so they feel well informed about the risks and how to mitigate them. There is a significant percentage of workers in the company who are reluctant to assume safe behavior practices during the process of installing fire systems and this is verified in the relationships with the dimensions of behavior (Recognition and positive reinforcement, observation and modeling and Integration of safe behavior (Habits)), so there is a strong to moderate positive relationship between safety management and the general behavior of workers, so Ho is rejected and H1 is accepted, that is, there is a significant relationship between safety management and the behavior of workers in the installation of fire protection systems at Mall Aventura Iquitos, Loreto.